Land use management by smallholders’ households as a promising way for synergies between the Rio Conventions: Case study in semi-arid areas of Cameroon - Kemeuze, V.A.; Sonwa, D.J.; Mapongmetsem, P.M.; Verchot, Louis V.; Fongnzossie, E.F.; Nkongmeneck, B.A. (Springer, 2020)
Land use management by smallholders’ households in dry landscapes can be an important entry point for contending desertification, climate change mitigation and biodiversity conservation. Strategies employed by these households to address land use problems can bring together efforts of the three Rio conventions. Identifying the typology of the current land use can lead to understand how biomass can be managed toward climate change mitigation efforts such as Clean Development Mechanism and Reduce Emissions from Deforestation and Forest Degradation including conservation, sustainable management of forests and enhancement of forest carbon stocks. From this perspective, a survey of 598 households in six divisions in the Far North Cameroon was conducted using a semi-structured questionnaire. This study reveals six main land uses, some of which overlap: cropped field (managed by 95% of local households), grassland (34%), settlements (28%) and forest lands (76%) that significantly contribute to local livelihoods. Non-timber forest products, fuelwoods, timbers and fodders are the main products provided by these land uses. Besides the products, some management practices including agroforestry, urban and peri-urban forestry and forest plantation have been identified to contribute to combat desertification and conserve biodiversity and climate change mitigation and adaptation in this semi-arid area of Cameroon.